Influence of the variability of the Kuroshio, the Oyashio, and the Pacific decadal oscillation on the northern hemisphere atmospheric circulation during the cold season - Révelard, Adèle (HAL CCSD, 2017)
The aim of this work is to study the influence on the atmosphere of the variability of the oceanic fronts associated with the Kuroshio and Oyashio Extensions (KE and OE), and to differentiate it from the influence of the main SST mode of the North Pacific, in particular the Pacific Decadal Oscillation (PDO). We use the atmospheric reanalysis ERA-Interim starting from 1979, and indices that describe the variability of the KE and OE that are already available. In the first part of this work, we focus on the KE influence, using lag partial regression analysis with the ENSO signal removed. We show that in October to January the positive phase of the KE leads to a downstream barotropic high response in the central North Pacific and over western United States, and an enhanced polar vortex. We try to understand the mechanisms behind this atmospheric response analyzing the KE influence on the synoptic activity. In the second part, we use a multivariate statistical method that allows us to analyze in parallel the atmospheric response to different oceanic forcings that may be correlated to each other. In addition to the KE and OE indices, we include in the analysis the main modes of SST variability of the tropical and northern hemisphere oceans, such as the PDO in the North Pacific and ENSO in the tropical Pacific. We also include sea ice variability in the Arctic. The atmospheric response being very dependent on the mean background flow, we distinguish between three seasons: early winter (OND), winter (DJF) and late winter (FMA). L'objectif de cette thèse est d'étudier l'influence sur l'atmosphère de la variabilité des fronts océaniques associés aux extensions du Kuroshio (KE) et de l'Oyashio (OE), et de la différencier de l'influence des modes de variabilité grande échelle de la SST du Pacifique Nord, en particulier l'oscillation décennale du Pacifique (PDO). Nous utilisons pour cela la réanalyse atmosphérique ERA-Interim à partir de 1979, et des index déjà disponibles décrivant la variabilité des courants. Dans une ...